2007
DOI: 10.1101/lm.516507
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of hippocampal mossy fibers is selectively induced seven days after the acquisition of a spatial but not a cued reference memory task

Abstract: Relating storage of specific information to a particular neuromorphological change is difficult because behavioral performance factors are not readily disambiguated from underlying cognitive processes. This issue is addressed here by demonstrating robust reorganization of the hippocampal mossy fiber terminal field (MFTF) when adult rats learn the location of a hidden platform but not when rats learn to locate a visible platform. Because the latter task requires essentially the same behavioral performance as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 36 publications
6
58
0
1
Order By: Relevance
“…To the best of our knowledge, very few studies have examined the influence of spatial learning on structural plasticity in this brain area. An increase in spine density within the molecular layer (44) and a sprouting of the mossy fiber sprouting within the CA3 subfield (45,46) are consistent with the effects reported here.…”
Section: Discussionsupporting
confidence: 80%
“…To the best of our knowledge, very few studies have examined the influence of spatial learning on structural plasticity in this brain area. An increase in spine density within the molecular layer (44) and a sprouting of the mossy fiber sprouting within the CA3 subfield (45,46) are consistent with the effects reported here.…”
Section: Discussionsupporting
confidence: 80%
“…In this study we demonstrate that the molecular processes regarded as crucial for long-term stabilization of information are needed within this structure for spatial but not cue learning. This dissociation is similar to what is observed in the hippocampus (40). However, differently from the hippocampus, VS manipulations also impair responding to cues in auto-shaping, in Pavlovian-instrumental transfer, or in the early stages of instrumental conditioning, coherently with the high number of reward-responding neurons in this structure but not in the hippocampus (41).…”
Section: Discussionsupporting
confidence: 61%
“…In this regard, it has been demonstrated that morphological rearrangements of dendrite spines and axonal redistribution in the hippocampus and cortex could occur after a variety of learning experiences (17). Accordingly, it has been demonstrated that axonal rearrangements in the mossy fibers of the hippocampus take place after several days of spatial water maze learning (11). However, these axonal rearrangements were not seen when animals were submitted to response implicit cue learning (11).…”
Section: Remodeling Of Neuronal Circuits By Experiencementioning
confidence: 99%
“…Accordingly, it has been demonstrated that axonal rearrangements in the mossy fibers of the hippocampus take place after several days of spatial water maze learning (11). However, these axonal rearrangements were not seen when animals were submitted to response implicit cue learning (11). In other words, the axonal rearrangement was seen only when animals consolidated explicit but not implicit spatial memory components.…”
Section: Remodeling Of Neuronal Circuits By Experiencementioning
confidence: 99%
See 1 more Smart Citation